Mobile Swab Collection Vehicle; a Blend of Necessity, Innovation, and Technology in a Resource-poor Country - Neopane, Arun Kumar; Shrestha, Sailendra Kumar Duwal; Dangol, Suman Raj; Shrestha, Bikal; Dutta, Ashis; Adhikari, Galav; Mandal, Jenny; Khadka, Hem Raj; Dhakal, Shanker (Journal of Nepal Health Research Council, 2021)
Mobile Swab Collection Vehicle is a concept that has been innovated by a team of medical and non-medical personals based upon the dire need to perform throat or nasopharyngeal swab collections to do reverse transcription polymerase chain reaction  ‘RT-PCR’ quickly, safely, and comfortably during this Corona Virus Diseases 2019, ‘COVID-19’ pandemic in a resource-poor country like Nepal. Inputs from the health care workers, beneficiaries, and engineers have been taken to construct this vehicle-mounted booth for swab collection. This vehicle is the ‘first of its kind’ in Nepal. Keywords: COVID-19; Nepal; swab collection vehicle